(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study examined the trends in skin temperature, Stratum Corneum Water Content (SCWC), Transepidermal Water Loss (TEWL) and subjective sensations during running exercises. Ten healthy male subjects performed exercises wearing cotton briefs in a climate chamber controlled at an air temperature of 27 ∼ 28 °C and a relative humidity of 50%. Following a rest for 20 mins on a chair (Rest), subjects exercised on a motorised treadmill at 4 km/h walking speed for 20 mins (walk) followed by a 7.2 km/h (medium run) and 12 km/h (high run) running speed for 10 min, respectively. The SCWC and TEWL were measured at pre-exercise, end-walk, end-medium run and end-high run. Skin temperatures were obtained by infrared thermograms for every 5 mins. The main findings were summarized as follows: Skin temperature in chest, abdomen, under arm, upper arm, forearm, hand, ventral thigh and ventral leg were significantly lower during walk, medium & high run than at rest by 0.13 ∼ 0.73, 0.36 ∼ 1.78, 0.35 ∼ 2.24 °C, respectively. Skin temperature in dorsal thigh, popliteal fossa was lower within 1? or higher by 0.11 ∼ 1.28 °C in dorsal leg and foot during exercises than at rest. In accordance with the regions of declines of skin temperatures, SCWC and TEWL doubled and elevated four times. Exercises were rated significantly higher for perception of humidity, heat and overall discomfort than rest. We discussed how dynamic exercises induce significantly different skin temperature, SCWC and TEWL on human body, which have profound influence on subjective perception of thermal factors, humidity and discomfort. The results of this study suggested that fall in skin surface temperature during dynamic exercising were related to thermal factors, such as evaporation due to skin sweat.